2015
DOI: 10.1186/s12889-015-1346-9
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for Young & Strong: a cluster randomized design to increase attention to unique issues faced by young women with newly diagnosed breast cancer

Abstract: BackgroundEach year, approximately 11% of women diagnosed with breast cancer in the United States are 45 years of age or younger. These women have concerns specific to or accentuated by their age, including fertility-related concerns, and have higher rates of psychosocial distress than women diagnosed at older ages. Current guidelines recommend that fertility risks be considered early in all treatment plans; however, the extant research indicates that attention to fertility by the healthcare team is limited. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 42 publications
0
51
0
1
Order By: Relevance
“…The findings suggest that preferences were driven in part by the young age of these women at the time of diagnosis; young age may involve different life factors and stressors (e.g., young children, education, working) than those facing women diagnosed at an older age (Greaney et al. ). In addition, because young women are more likely to get aggressive cancer treatments than older women, their experiences of these treatments may differ, potentially influencing these views on what information would be valuable at what times and how capable they would have been of handling that information.…”
Section: Resultsmentioning
confidence: 98%
“…The findings suggest that preferences were driven in part by the young age of these women at the time of diagnosis; young age may involve different life factors and stressors (e.g., young children, education, working) than those facing women diagnosed at an older age (Greaney et al. ). In addition, because young women are more likely to get aggressive cancer treatments than older women, their experiences of these treatments may differ, potentially influencing these views on what information would be valuable at what times and how capable they would have been of handling that information.…”
Section: Resultsmentioning
confidence: 98%
“…Cluster-randomization trials (CRTs), by contrast, are better suited for digital solutions supporting group efforts (e.g. solutions supporting tumor board meetings 39 ), and this approach has been increasingly adopted by public health researchers [40][41][42] . CRTs are often used in situations when contamination may occur; for example, where individuals in the same cluster have been randomized to different intervention groups, or for logistic, feasibility or ethical reasons 43 .…”
Section: Surveys and Interviewsmentioning
confidence: 99%
“…Baseline assessment often occurred at the first medical oncology visit for the participants. Details on the trial can be found in previous publications [27,28].…”
Section: Study Populationmentioning
confidence: 99%